Parosmia and Neurological Disorders: A Neglected Association - Ciurleo, Rosella; De Salvo, Simona; Bonanno, Lilla; Marino, Silvia; Bramanti, Placido; Caminiti, Fabrizia (Frontiers in Neurology, 2020)
Parosmia is a distorted olfactory sensation in the presence of an odor. This olfactory disorder can affect the quality of life of most patients who experience it. Qualitative olfactory dysfunctions, such as parosmia and phantosmia, may be clinical conditions secondary to neurological diseases. The incidence of parosmia is underestimated, as well as its association with neurological diseases, due to poor self-reporting of patients and lack of objective methods for its measure. In this paper, we show selected clinical cases of parosmia associated with neurological disorders, such as traumatic brain injury and multiple sclerosis. These clinical cases show how the correct diagnosis of parosmia can represent the tip of the iceberg of important underlying neurological disorders and be a good prognostic indicator of their progression or recovery.